2021
DOI: 10.1111/hel.12810
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of Helicobacter pylori infection in Wuwei, a high‐risk area for gastric cancer in northwest China: An all‐ages population‐based cross‐sectional study

Abstract: Objective: This study aimed to determine the prevalence and risk factors of Helicobacter pylori infection across all age groups in Wuwei City, a high-risk area for gastric cancer in Northwest China. Methods:We conducted this study from 2016 to 2017 in an urban and a rural community in Wuwei City. Stool antigen tests targeted individuals aged 0 to 3 years old, and 13 C-urea breath tests targeted individuals aged above 3 years. We selected participants based on hierarchical cluster sampling. We assessed the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 42 publications
4
13
0
Order By: Relevance
“…Annual household income, history of smoking, history of alcohol consumption, dining location, and family history of gastric disease or GC were not different between the infected and non-infected groups, but individuals with a higher education level showed a lower infection rate. A 2020 all-ages population-based cross-sectional study[ 28 ] in Wuwei county in northwestern China showed that the prevalence of H. pylori infection was closely associated with socioeconomic conditions, sanitary situations, dietary habits of the participants in the city. Boarding, eating at school, and drinking untreated water were main factors explaining the rising infection rate in junior-senior high school students.…”
Section: Discussionmentioning
confidence: 99%
“…Annual household income, history of smoking, history of alcohol consumption, dining location, and family history of gastric disease or GC were not different between the infected and non-infected groups, but individuals with a higher education level showed a lower infection rate. A 2020 all-ages population-based cross-sectional study[ 28 ] in Wuwei county in northwestern China showed that the prevalence of H. pylori infection was closely associated with socioeconomic conditions, sanitary situations, dietary habits of the participants in the city. Boarding, eating at school, and drinking untreated water were main factors explaining the rising infection rate in junior-senior high school students.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 The prevalence of HP infection has been reported to increase with age, gradually increasing from 0 to 39 years, peaking at 39 years (59.3%) and gradually decreasing after 60 years. 3 HP was recognized as a group I human carcinogen by the World Health Organization’s International Agency for Research on Cancer. About 50% of gastric cancers are associated with HP.…”
Section: Introductionmentioning
confidence: 99%
“…We obtained the age-speci c gastric cancer incidence from Chinese literature about the 2012 cancer incidence analysis of Wuwei Municipality, Gansu Province, China [21]. We employed H. pylori prevalence according to an all-age population-based cross-sectional study in the Wuwei region [22]. The initial distributions of the cost-effectiveness analysis in different Markov states were determined from the Wuwei Cohort epidemiologic database (Supplementary Table S2).…”
Section: Input Parametersmentioning
confidence: 99%